Students’ problem-solving ability in hybrid learning using problem-based learning model: a case study - Lisandra, Yolla; Safarini TLS, Desyarti (International Journal of Mathematics and Sciences Education, 2023)
This study aimed to describe the process of learning mathematics in hybrid learning using a problem-based learning model. Furthermore, investigate the performance of students' problem-solving abilities in hybrid learning using problem-based learning. This case study research was conducted in one of the secondary schools in Bogor, Indonesia with a total of 20 students (13-15 years old) and a sample of six students who were selected based on convenience sampling. Data were collected through participant observation and written test. Researchers carry out problem-based learning on the material of a two-variable system of linear equations. The results showed that the hybrid learning process went smoothly. Students were enthusiastic about new media of learning. However, researchers found differences in the strategies used by students at home and school. Students' problem-solving ability to understand the problem is in a good category; devising a plan has a good enough category; carrying out a plan is not good enough; looking back is still in the very poor category.